2012
DOI: 10.1890/es12-00241.1
|View full text |Cite
|
Sign up to set email alerts
|

Divergent carbon dynamics under climate change in forests with diverse soils, tree species, and land use histories

Abstract: Abstract. Accounting for both climate change and natural disturbances-which typically result in greenhouse gas emissions-is necessary to begin managing forest carbon sequestration. Gaining a complete understanding of forest carbon dynamics is, however, challenging in systems characterized by historic over-utilization, diverse soils and tree species, and frequent disturbance. In order to elucidate the cascading effects of potential climate change on such systems, we projected forest carbon dynamics, including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 60 publications
3
43
1
Order By: Relevance
“…Similarly, predicting the impact of invasive insects on long-term forest C dynamics using process-based simulation models has been only partially successful. Although process-based models have accurately captured the effects of gypsy moth defoliation on tree biomass, stand species composition, and the dynamics of GEP and ANPP, they have generally underestimated the long-term reduction in NEP in forests of the PNR following disturbance [9][10][11]. For example, the Ecosystem Demography 2 Model parameterized for xeric hardwoods and conifers and to represent defoliation events and tree mortality at oak-dominated stands in the PNR over 200-year simulations indicated that defoliation intensity was linearly related to decreases in annual NEP, but also predicted that post-disturbance NEP exceeded 80 to 90 g C m −2 year −1 at all levels of defoliation [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, predicting the impact of invasive insects on long-term forest C dynamics using process-based simulation models has been only partially successful. Although process-based models have accurately captured the effects of gypsy moth defoliation on tree biomass, stand species composition, and the dynamics of GEP and ANPP, they have generally underestimated the long-term reduction in NEP in forests of the PNR following disturbance [9][10][11]. For example, the Ecosystem Demography 2 Model parameterized for xeric hardwoods and conifers and to represent defoliation events and tree mortality at oak-dominated stands in the PNR over 200-year simulations indicated that defoliation intensity was linearly related to decreases in annual NEP, but also predicted that post-disturbance NEP exceeded 80 to 90 g C m −2 year −1 at all levels of defoliation [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since abandonment, these regenerating forests have been moderate to strong sinks for atmospheric carbon dioxide (CO 2 ) [3][4][5][6][7]. In the mid-Atlantic region, estimates of net primary production (NPP) and net ecosystem production (NEP) for intermediate-age forests are highest for oak-hickory forests and lowest for pine-dominated forests [8][9][10]. Overall NEP has been projected to decline slowly as forests age across the region [1, 9,11,12], with productivity declining more slowly for hardwood-dominated forests than conifer-dominated forests [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) of LANDIS-II to simulate tree establishment, forest succession, and C and N cycling ( Fig. 2; Scheller et al 2011aScheller et al , 2012. This succession extension uses species-specific life history attributes and growth rates to model tree growth and regeneration, which helps determine successional changes in species composition.…”
Section: Description Of the Century Succession Extension Of Landis-iimentioning
confidence: 99%
“…The extension also simulates N leaching (dependent on precipitation, soil characteristics, and hydrologic flow rates) and denitrification, which is a function of available N (Scheller et al 2012). The extension also simulates the internal cycling of C and N through the vegetation (leaf, wood, fine roots, and coarse roots by species and age), detritus (foliar, woody, fine roots, and coarse roots), and soil (fast, slow, and passive pools) (Scheller et al 2011a(Scheller et al , 2012. The decomposition of C and mineralization of N is calculated separately in each of the detrital and soil pools.…”
Section: Description Of the Century Succession Extension Of Landis-iimentioning
confidence: 99%